Investigation of Microabrasion Wear Behavior of Boronized Stainless Steel with Nanoboron Powders - Gunen, Ali; Gok, M. Sabri; Erdogan, Azmi; Kurt, Bulent; Orhan, Nuri (Taylor & Francis Inc, 2013)
In this study, 304 stainless steel was boronized using nano boron powders using a solid-state box boronizing technique. Boronizing processes were carried out at temperatures of 950 and 1000 degrees C for 2 and 4h of treatment. Nano boron was used as a source of boron and KBF4 salt was used as an activator. The boxes in which boron was processed were made of 304 stainless steel plates. A free-ball microabrasion test was performed on the boronized samples. Silicon carbide (SiC) abrasive powders (5m) were used in the abrasion experiments. The ball rotational speed was 73.7, 102.5, and 147.4rpm in the free-ball microabrasion test. Boronized steels showed an improvement in abrasive wear resistance. Microstructures and wear surfaces of the samples were inspected using scanning electron microscopy (SEM) and optical microscopy. It was observed from SEM and optical examinations that boronizing time and temperature had an important effect on the thickness of the boride layer on steel surfaces. The presence of boride formed in the boride layer at the surface of the steels was determined by X-ray diffraction (XRD) analysis and (FeB, Fe2B) iron boride phases were observed. The microhardness values of the iron borides was up to 1626 HV. The abrasion rate for the boronized samples was quite high for abrasive and adhesive conditions due to a brittle layer with a nonuniform crystalline structure on the outer surface. Microchannels and rolling abrasions, which are characteristic of microabrasion, were determined as the abrasion mechanism.
Keywords: Boronizing; Microscale Abrasion; Free-Ball; FeB-Fe2B